2010
DOI: 10.1002/hipo.20884
|View full text |Cite
|
Sign up to set email alerts
|

A novel non‐CB1/TRPV1 endocannabinoid‐mediated mechanism depresses excitatory synapses on hippocampal CA1 interneurons

Abstract: Endocannabinoids (eCBs) mediate various forms of synaptic plasticity at excitatory and inhibitory synapses in the brain. The eCB anandamide binds to several receptors including the transient receptor potential vanilloid 1 (TRPV1) and cannabinoid receptor 1 (CB1). We recently identified that TRPV1 is required for long-term depression at excitatory synapses on hippocampal stratum radiatum interneurons. Here we performed whole-cell patch clamp recordings from CA1 stratum radiatum interneurons in rat brain slices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 81 publications
0
35
0
Order By: Relevance
“…In a previous study, our lab identified an anandamide‐mediated plasticity that was independent of CB1 and TRPV1 (Edwards et al, ). Therefore, we chose to examine GPR55 as a candidate for this effect based on its ability to bind eCBs such as anandamide and the fact that lysophosphatidylinositol has never been examined for its role in plasticity that we know of.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, our lab identified an anandamide‐mediated plasticity that was independent of CB1 and TRPV1 (Edwards et al, ). Therefore, we chose to examine GPR55 as a candidate for this effect based on its ability to bind eCBs such as anandamide and the fact that lysophosphatidylinositol has never been examined for its role in plasticity that we know of.…”
Section: Discussionmentioning
confidence: 98%
“…However, this compound and endocannabinoids might modify synaptic transmission and induce synaptic plasticity through CB1 receptorindependent actions (Edwards et al 2012;Golovko et al 2015). We have performed several sets of experiments to examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…LTD of glutamatergic inputs onto hippocampal interneurons can also be triggered by several induction protocols (McMahon and Kauer, 1997; Laezza et al, 1999; Gibson et al, 2008; Nissen et al, 2010; Le Duigou et al, 2011; Edwards et al, 2012). When tested, LTD in cortical GABAergic interneurons was found to be insensitive to treatment with CB 1 antagonists (Lu et al, 2007; Gibson et al, 2008; Edwards et al, 2010; Le Duigou et al, 2011), which was surprising, because synthetic cannabinoid ligands effectively suppress excitatory inputs onto hippocampal interneurons including fast-spiking basket cells (Gibson et al, 2008; Holderith et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its high postsynaptic concentration opposing presynaptic CB 1 cannabinoid receptors at excitatory synapses of hippocampal principal cells (Katona et al, 2006; Yoshida et al, 2006), and tight coupling of group I mGlu-activation to 2-AG mobilization (Jung et al, 2005), mGlu-dependent LTD at hippocampal excitatory synapses is generally considered to be endocannabinoid-independent in principal cells (Rouach and Nicoll, 2003; Nosyreva and Huber, 2005; Lante et al, 2006). Similarly, excitatory synapses onto hippocampal and other cortical interneurons can readily undergo LTD (McMahon and Kauer, 1997; Laezza et al, 1999; Lu et al, 2007; Gibson et al, 2008; Nissen et al, 2010; Le Duigou et al, 2011; Edwards et al, 2012), but DGL-α has not yet been reported in GABAergic interneurons, and pharmacological experiments suggest that LTD in cortical interneurons may not require endocannabinoid signaling (Lu et al, 2007; Gibson et al, 2008; Le Duigou et al, 2011; Edwards et al, 2012). …”
Section: Introductionmentioning
confidence: 99%